Information Technology Utilization on the Performance of Sharia Bank Employees in Palopo City - Mujahidin, Mujahidin; Majid, Nurul Huda Abdul (IKONOMIKA, 2021)
This study aims to examine the impact of information technology on the performance of Sharia Bank employees in Palopo City. The world is entering the industrial era known as 4.0 in which human activities rely on information and communication technology. The internet has also become an inseparable part of it. This study used a quantitative method by administering questionnaires to the respondents. The results showed that information technology has a significant impact on the performance of Sharia Bank in Palopo City. percentage of the influence of information technology on the performance of sharia bank employees in Palopo City is 59.1%. The increasing performance of the employees has an impact on the company profits and encourages the investments. Plenty invesment will create a wide employment opportunities for the community and have an impact on economic growth. It will  in turn create prosperity and walfare for a nation.